Peranan Federasi Serikat Perempuan Merdeka (FSPM) Dalam Penanganan Tindak Kekerasan Terhadap Perempuan - Humala Simangunsong (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
This study uses a qualitative method. Research location at FSPM Office of Deli Serdang Regency. The research informants were members related to the handling of cases of violence against women. The focus of the research is the efforts of FSPM of Deli Serdang Regency in dealing with violence against women, with indicators: education and training, medical elements, community awareness, cooperation with other parties. Data collection tools used in this study are interviews and documentation. Data collected using interaction analysis model. The results of the research show that the efforts of the Federation of Free Women's Unions (FSPM) in Handling Violence Against Women, among others through: education and training, medical elements, community awareness, cooperation with other parties (Police, NGOs, CSOs) FSPM of Kabupaten Deli Serdang, it can be concluded that the role of FSPM on violence against women is maximal, this can be observed from the resolution of cases of violence against women in 2015-2016, out of 20 cases, 16 cases resolved, 4 cases still in handling process Based on the results of this research, it is hoped that the FSPM of Deli Serdang Regency is suggested that the FSPM of Kabupaten Deli Serdang is more active to socialize their role to the community so that the community will know the types of violence and the violence and the process of handling the violence of women. Keywords: Role, FSPM, Violence, Violence Against Women